Trailblazing women printmakers : Virginia Lee Burton Demetrios and the Folly Cove Designers - Sarni, Elena M., 1976- (New York : Princeton Architectural Press, 2023)
"The history of the Folly Cove Designers (1941-1969)-one of America's longest-running artist collectives-is explored through their work"--
boek
Keywords: Folly Cove Designers; Burton Demetrios, Virginia Lee